2007
DOI: 10.1016/j.jvs.2007.02.073
|View full text |Cite
|
Sign up to set email alerts
|

Persistent type 2 endoleak after endovascular repair of abdominal aortic aneurysm is associated with adverse late outcomes

Abstract: Persistent type 2 endoleak is associated with an increased incidence of adverse outcomes, including aneurysm sac growth, the need for conversion to open repair, reintervention rate, and rupture. These data suggest that patients with persistent type 2 endoleak (>6 months) should be considered for more frequent follow-up or a more aggressive approach to reintervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
303
1
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(317 citation statements)
references
References 36 publications
7
303
1
6
Order By: Relevance
“…9,17,18 Even when feeding patent vessels are not clearly present, but when there is evidence of sac enlargement, authors have shown concern about the risk of rupture and the evolution of sac dimensions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,17,18 Even when feeding patent vessels are not clearly present, but when there is evidence of sac enlargement, authors have shown concern about the risk of rupture and the evolution of sac dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] However, given the consistent percentage of stable or regressive type II endoleak, the need for treatment remains controversial. 4,6,9 According to the European Collaborators on Stent-Graft Techniques for Abdominal Aortic Aneurysm Repair (EUROSTAR) database, most type II endoleaks will thrombose spontaneously and have a benign course. 8 Treatment is considered only for large, high-flow endoleaks or in case of aneurysmal growth.…”
mentioning
confidence: 99%
“…This constitutes a strong argument for selective preoperative endovascular intervention in view of the substantial risk of persistent type II endoleak. 23) To determine the indication of selective intervention of the IMA prior to EVAR, preoperative CT constitutes the most reliable and easily available image source. Univariate analysis of the anatomical variables of preoperative CT revealed that stenosis and thrombus of the IMA orifice is associated with both transient and permanent type II endoleak.…”
Section: Discussionmentioning
confidence: 99%
“…Although most T2Es resolve spontaneously within a few months or remain benign, [9][10][11][12] persistent T2Es can be associated with sac expansion and, therefore, require secondary intervention 10 to avoid rupture. Currently, two major endovascular techniques exist for the management of T2Es: direct translumbar embolization (TLE) and transarterial embolization (TAE).…”
Section: Type II Endoleak Following Endovascular Repair Of Infrarenalmentioning
confidence: 99%